A bi-level co-expansion planning of integrated electric and heating system considering demand response - Du, Yuan; Xue, Yixun; Lu, Lina; Yu, Canping; Zhang, Jiangfeng (Frontiers in Energy Research, 2022)
With the wide deployment of combined heat and power units, electric boilers, etc., the power system and the heating system are coupled tightly, which necessitates expansion planning in a coordinated manner. Demand response (DR) is considered an effective method for augmenting system flexibility, which would lead to a more beneficial planning strategy in the co-expansion planning strategy. Therefore, we develop a bi-level co-expansion planning model with DR constraints for the integrated electric and heating system to minimize expenses on both investment and operation. The upper level gives the optimal investment strategy of energy facilities, while the lower level is optimal operation problems with DR constraints under the given investment decision. Numerical simulation is employed in the P6H8 system to demonstrate the proposed model.